Promoting employment among older Koreans : healthy ageing, work and fiscal impacts - Lee, Eunkyeong (The Korea Institute of Public Finance SeoulKR, 2013)
Leads the discussion on whether higher life expectancy contributes to increased healthy life expectancy. Examines the effects of the health status of aged persons on the labour market using the Korean Longitudinal Study of Ageing (KLoSA). Examines the increase in the labour supply for a possible influence on government's fiscal status. Illustrates the result of empirical research and present the conclusion and policy implications.